(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the treatment outcomes of endoscopic retrograde cholangiopancreatography (ERCP) in patients with severe acute cholangitis due to bile duct stones at Can Tho Central General Hospital. Methods: A descriptive cross-sectional study with longitudinal follow-up was conducted on 90 patients with severe acute cholangitis due to bile duct stones who underwent ERCP at Can Tho Central General Hospital from June 2024 to January 2026. Results: The mean age was 68.83 ± 14.35 years, with females accounting for 62.2%. Abdominal pain was present in all patients (100%). Laboratory parameters reflecting infection, biliary obstruction, and liver enzymes were all elevated. The success rate of ERCP was 98.9%. Simple stone extraction was the most common technique, accounting for 65.2%. The overall complication rate after ERCP was 12.22%, with post-ERCP pancreatitis being the most frequent complication (11.11%). Multivariate logistic regression analysis showed that a history of previous ERCP remained significantly associated with post-ERCP pancreatitis (OR = 5.868; 95% CI: 1.124–30.630; p = 0.036). Conclusion: Endoscopic retrograde cholangiopancreatography is a treatment modality with a high success rate and a low complication rate in patients with severe acute cholangitis due to bile duct stones in this study sample.